Analisis Dampak Lingkungan Kelas terhadap Konsentrasi Belajar Siswa - Simbolon, Elisabet; Taofik, Taofik; Soleh, Dudung Amir (Irsyaduna: Jurnal Studi Kemahasiswaaan, 2025)
The classroom environment plays a significant role in determining the success of learning processes, especially regarding students’ concentration. Concentration is a crucial factor that influences how well students can absorb and understand learning materials. This article is presented as a literature review aimed at evaluating the impact of various physical aspects of the classroom on students’ ability to maintain focus throughout the learning process. The research uses a literature review approach, involving the collection, examination, and analysis of relevant previous studies. The review findings indicate that factors such as adequate lighting, comfortable room temperature, low noise levels, and a well-organized classroom layout significantly affect students' concentration levels. Therefore, designing classrooms with attention to these physical elements is a key strategy in creating a learning atmosphere that is both conducive and effective, especially at the elementary education level